Non-Pharmaceutical Interventions May Attenuate Acute Exacerbations of Asthma: Experience During the COVID-19 Pandemic in Taiwan - Lin CY; Lin CH; Lo YL; Lo CY; Huang HY; Hsieh MH; Fang YF; Li TC; Lin SM; Huang YT; Chang PJ; Lin HC (Journal of Asthma and Allergy)
Chun-Yu Lin,1,2 Chiung-Hung Lin,1,2 Yu-Lun Lo,1,2 Chun-Yu Lo,1,2 Hung-Yu Huang,1,2 Meng-Heng Hsieh,1,2 Yueh-Fu Fang,1,2 Tsu-Chuan Li,1,2 Shu-Min Lin,1,2 Yu-Tung Huang,3 Po-Jui Chang,1,2 Horng-Chyuan Lin1,2,4 1Department of Thoracic Medicine, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan; 2College of Medicine Chang Gung University, Taoyuan, Taiwan; 3Center for Big Data Analytics and Statistics, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 4Department of Respiratory Therapy, Chang Gung Memorial Hospital at Linkou, Taoyuan, TaiwanCorrespondence: Horng-Chyuan Lin, Department of Thoracic Medicine, Chang Gung Memorial Hospital, 5 Fu-Hsing Street, Kweishan, Taoyuan, 33305, Taiwan, Tel +886-3-3281200 ext. 8470, Fax +886-3-3282474, Email lin53424@gmail.comBackground: Non-pharmaceutical interventions (NPIs) were widely used during the coronavirus disease 2019 (COVID-19) pandemic, however their impact on acute asthma exacerbations (AEs) is not well studied.Methods: We had retrospectively collected patients with asthma AEs between 2019 and 2020 and retrieved data from the Chang Gung Research Database, including clinical manifestations, medications, pulmonary function, clinic and emergency department visits and hospitalizations.Results: A total of 39,108 adult patients with asthma were enrolled, of whom 1502 were eligible for analysis. The prevalence of acute AEs significantly decreased throughout 2020 compared with 2019 after implementation of the NPI policy. The patients were categorized into four groups: Group 1, acute AEs in 2019 with influenza infection (n=692); Group 2: acute AEs in 2019 without influenza infection (n=328); Group 3: acute AEs in 2020 with influenza infection (n=268); Group 4: acute AEs in 2020 without influenza infection (n=214). The patients in group 4 were significantly older (73.3± 29.1 vs 65.5± 29.2, 69.7± 26.2 years, p< 0.01) and had significantly worse forced expiratory volume in one second/forced vital capacity ratio (70.5± 13.9 vs 79.6± 15.5, 72.9± 18.0, p< 0.01) than those in group 1 and 2, and the highest rate of oral corticosteroid prescriptions (17%, p< 0.01). The patients in group 3 and 4 had significantly lower rates of oxygen therapy, ventilator use and mortality at 3 and 12 months of follow-up than those in group 1 and 2.Conclusion: The use of NPIs during the COVID-19 pandemic in Taiwan may reduce the frequency and severity of asthma AEs. This may provide some cost-effective strategies to attenuate acute asthma AEs.Keywords: non-pharmaceutical interventions, asthma, COVID-19